Recent Survey on Nanosuspension: A Patent Overview - I. Jethara, Sahilhusen; D. Patel, Alpesh; R. Patel, Mukesh; S. Patel, Mukesh; R. Patel, Kanu (Recent Patents on Drug Delivery & Formulation, 2015)
The major goals of designing nanosuspension of nanosize materials are increasing due to their tremendous potential as a drug delivery system with the wide range of applications. Nanosuspension is a unique tool for improving the bioavailability of poorly soluble drugs. Nanosuspension drug delivery has wide range of application like oral, injectable, transdermal, inhalation, peroral, ocular, pulmonary and topical etc. by improviing the bioavailability, reducing the dose, gastric irritation, decreasing intra subject variability and increasing adhesivness with intestinal membrane. Recently, nanosuspension has been received much interest as a way to resolve solubility and stability problem because of their cost-effectiveness and technical simplicity compare to other liposome and colloidal drug carriers. Nanosuspensions are engaged to control particle size, surface properties and release of pharmacologically active agents in order to achieve the site-specific action of the drug at the therapeutically optimal rate, improve the bioavaibility of drug with poor solubility and dose regimen. Application and preparation method of nanosuspension has been reported by research articles and patented in different countries. Most of the marketed nanosuspensions are in preclinical and clinical based study for its application. More than 100 patents have been published on nanosuspensions by the recent days. This patent reviews covers different methods of pharmaceutical preparation and applications in drug delivery as well as the recent marketed published or granted patent surveys. This patent review is useful in enhance the knowledge of controlled drug delivery and applications.
Keywords: nanosuspension